Place Identity Of The Traditional Courtyard “Late Straits” Eclectic Style Shophouses, George Town Heritage City, Penang - Zwain, Akram M. Ali Mahdi (2021)
This study aimed at investigating the place identity which refers to architectural, cultural, and environmental aspects of the traditional courtyard shophouses in George Town, Malaysia. Also, the study proposed a checklist of courtyard architectural characteristics for sustainability and documentation that would reflect the place identity of the Straits Chinese.